ANALISIS POLA KONSUMSI DAN INDEKS MASSA TUBUH PADA STUDI KOHOR DI BOGOR - Retiaty, Fifi; Palupi, Nurheni Sri; Ernawati, Fitrah; Andarwulan, Nuri (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2024)
Body Mass Index (BMI) is a commonly used indicator to assess nutritional status, which can be influenced by nutrient intake from food consumption. This study aims to analyze the relationship between energy and macronutrient intake and BMI. A cross-sectional design was applied using data from the 2019 Non-Communicable Disease Risk Factor Cohort Study (FRPTM), involving 1,018 subjects selected purposively from a total of 1,218 respondents. The data analyzed included sociodemographic characteristics, BMI, and 1x24-hour dietary recall. Descriptive and bivariate analyses were conducted using the Kruskal-Wallis test, followed by the Mann-Whitney test for variables showing significant differences. The results indicated significant associations between BMI and gender, energy intake (low vs. high), fat intake (adequate vs. high), and carbohydrate intake (low vs. adequate and low vs. high). These differences may be influenced by variations in metabolism and intake levels. In conclusion, BMI is affected not only by energy and macronutrient intake but also by other contributing factors.